ความรับผิดทางละเมิดของผู้ประกอบวิชาชีพเวชกรรม - ภุมรินทร์ ศรีมูล (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
In cases arising from the practice of medical professionals, a victim often faces an insurmountable obstacle of proving a wrongful act. This is especially true for cases arising from negligent acts in the course of a treatment. Such a tortuous act cannot be proven easily despite past studies on professional standards for various professions and proposals for the application of the principles of professional liability to tortuous liabilities of professional practitioners, the attraction being the allocation of the burden of proof on the practitioner to justify his acts. The adoption by analogy of this principle to the Thai legal system was made possible by the principles of the assumption of liability under section 422 of the Civil and Commercial Code, where a similar result could be achieved as under the professional liability principle. However, the coming into force of two Acts, namely the Tortuous Liabilities of Officials Act, B.E. 2539 (1996), and the National Health Security Act, B.E. 2545 (2002), created a divide in the standards of liability of medical professionals in public medical facilities and medical professionals in private medical facilities, undermining the effectiveness of applying professional liability principles. The enactment of a specific law on tortuous liabilities of medical professionals which adopts the assumption of liability together with an establishment of a fund for providing compensation to victims of negligent acts by medical professionals, and the amendment of the National Health Security Act, B.E. 2545 (2002), to restrict the right to seek indemnification only in cases of intentional acts or gross negligence, coupled by the engendering of a good understanding of the roles of medical practitioners whose practice draws them closer to the service recipients than any other profession and the recognition of the recipient’s rights as a victim to claim compensation for the tortuous acts, would result in a protection of the patient’s life and health, including the determination of the scope of liability for medical professionals, which would be more comprehensive and just.